Infection of scots pine afforestations (Pinus sylvestris L.) by annosum root rot (Heterobasidion annosum (fr.) Bref.) in the eastern german lignite district = Infekcja zadrzewień sosny zwyczajnej (Pinus sylvestris L.) wywołane przez korzeniowca wieloletniego (Heterobasidion annosum (Fr.) Bref.) w okręgu wydobywczym węgla brunatnego we wschodnich Niemczech - Knoche, Dirk; Ertle, Christoph (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During the last years an alarming dieback has occurred in 20 to 40 years old first-rotation pine stands (Pinus sylvestris L.) on mine sites, caused by the white rot fungus Heterobasidion annosum (Fr.) Bref. First thinning opens the infection path so that up to now 30 to 89 % of afforestations in different mining areas are affected.
Keywords: zadrzewienia; sosna zwyczajna; korzeniowiec wieloletni (Heterobasidion annosun); Pine afforestation; Annosum root rot; forest dieback; mine soil; water storage capacity; soil pH